2012
DOI: 10.1254/jphs.11153fp
|View full text |Cite
|
Sign up to set email alerts
|

Novel Action of the Chalcone Isoliquiritigenin as a Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) Inhibitor: Potential Therapy for Cholera and Polycystic Kidney Disease

Abstract: Abstract. Overstimulation of cAMP-activated Cl− secretion can cause secretory diarrhea. Isoliquiritigenin (ISLQ) is a plant-derived chalcone that has a wide range of biological activities. The present study thus aimed to investigate the effect of ISLQ on cAMP-activated Cl − secretion in human intestinal epithelium, especially the underlying mechanism and therapeutic application. Short-circuit current analysis of human intestinal epithelial (T84) cell monolayers revealed that ISLQ dose-dependently inhibited cAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 38 publications
0
15
1
Order By: Relevance
“…A recent study by Hoque et al (2010) raises a possibility that CFTR and IRC equally contribute to cAMP-activated Cl − secretion in T84 cells (Hoque et al, 2010). However, using a CFTR-specific CFTR inhibitor isoliquiritigenin (ISLQ), we recently found that cAMP-induced Cl − secretion in T84 cell monolayers was completely inhibited by ISLQ, suggesting the sole contribution of CFTR to the cAMP-activated Cl − secretion (Muanprasat et al, 2012). In addition, IRC-mediated apical Cl − current during cAMP stimulation was observed only after CFTR was inhibited by CFTR inh - 172 (Muanprasat et al, 2012).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…A recent study by Hoque et al (2010) raises a possibility that CFTR and IRC equally contribute to cAMP-activated Cl − secretion in T84 cells (Hoque et al, 2010). However, using a CFTR-specific CFTR inhibitor isoliquiritigenin (ISLQ), we recently found that cAMP-induced Cl − secretion in T84 cell monolayers was completely inhibited by ISLQ, suggesting the sole contribution of CFTR to the cAMP-activated Cl − secretion (Muanprasat et al, 2012). In addition, IRC-mediated apical Cl − current during cAMP stimulation was observed only after CFTR was inhibited by CFTR inh - 172 (Muanprasat et al, 2012).…”
Section: Discussionmentioning
confidence: 92%
“…However, using a CFTR-specific CFTR inhibitor isoliquiritigenin (ISLQ), we recently found that cAMP-induced Cl − secretion in T84 cell monolayers was completely inhibited by ISLQ, suggesting the sole contribution of CFTR to the cAMP-activated Cl − secretion (Muanprasat et al, 2012). In addition, IRC-mediated apical Cl − current during cAMP stimulation was observed only after CFTR was inhibited by CFTR inh - 172 (Muanprasat et al, 2012). This data suggest that CFTR inhibition alone may not be sufficient to completely inhibit intestinal fluid secretion in cholera, since cholera toxin-induced apical Cl − efflux could escape CFTR blockage by using IRC as an alternative route.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activation of the NSC channel by catecholamine is not directly mediated by PKA (71). cAMP, the concentration of which is increased by catecholamine, activates K + and Cl − channels directly and also indirectly via a PKA-mediated pathway (10,121,122) (Fig. 1).…”
Section: +mentioning
confidence: 99%
“…3,4) CFTR inhibitors have been shown to effectively inhibit fluid loss in rodent models of cholera and to reduce renal cyst progression in mouse models of polycystic kidney disease. 5,6) CFTR exists in a macromolecular complex consisted of several interacting partners including regulatory proteins such as protein kinase A (PKA) and adenosine monophosphate (AMP)-activated protein kinase (AMPK). 7,8) Activation of a cAMP-dependent PKA stimulates CFTR activity via phosphorylation at a regulatory (R) domain.…”
Section: Cystic Fibrosis Transmembrane Conductance Regulator (Cftr) Imentioning
confidence: 99%